Implementasi Program Asesmen Nasional Di Sekolah Dasar: Asesmen Nasional - Ema Astri Muliasari; Seni Apriliya; Erwin Rahayu Saputra (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
Starting in 2021, a National Assessment will be held in Indonesia, one of which is the Minimum Competency Assessment (AKM). The Minimum Competency Assessment is implemented based on the results of the 2018 PISA study, which shows that the ability of Indonesian students in reading, mathematics, and science is still below average. Therefore, the purpose of this study was to analyze the National Assessment program and its implementation in elementary schools. This research is in the form of descriptive qualitative research where the data is taken from interviews, observations, questionnaires, and documentation studies. The research subjects were principals, classroom teachers, and elementary school students in Tasikmalaya City. From the results of the analysis, it was found that there was still a lack of school readiness, especially in the availability of infrastructure and the absence of school programs in facing the National Assessment. Therefore, an analysis is necessary as a basis to formulate a sustainable program in facing the National Assessment.